Transformative learning theory for leadership development coaching in an automotive manufacturing organisation in South Africa - Jozaffe-Naidoo, Genevieve (My University, 2021)
The business environment faces constant change, complexity and ambiguity. Leaders are faced with unprecedented times in which they have to navigate uncertainty, yet they are expected to lead their teams from a knowing position. In addition to this formidable challenge, in the South African context, are the covert struggles of inequity. The lack of equitable representation on all levels, within the organisation being studied, as is the case in other South African organisations, inspired this research. This study focuses on the application of transformative learning theory during leadership coaching to facilitate an organisational culture centred on diversity, inclusion and equality, which is meant to improve employee engagement. Equality and diversity practices, for the purpose of workplace inclusion, are common in improving business performance within the modern organisation. Moreover, global movements in response to racial, gender, sexual orientation and other forms of prejudice beg the question: should a different approach be explored in overcoming obstacles to employee engagement, so as to enhance organisational culture and a sense of belonging? In the automotive manufacturer employed for the purpose of this study, challenges on diversity and equality affect promotion, development and employee engagement, all of which require leadership intervention in order to attract and retain talent for organisational viability. To investigate leadership’s role in workplace inclusion, the study used a qualitative action research approach to gather evidence on the application of transformative learning during leadership development coaching so as to improve employee engagement. The leaders selected for participation in this study work within the same division but operate at various levels of seniority – that is, middle, senior and executive management. Their direct reports participated in focus group sessions prior to the commencement of leadership coaching, in order to elicit existing organisational contexts and background on leadership behaviour pertaining to workplace inclusion. After the leadership coaching intervention, focus group sessions were hosted to confirm changes in leadership behaviour related to inclusion practices. First, the findings show that the application of transformation learning theory during leadership development coaching is multifaceted; in this respect, stimulating a disorienting dilemma can be incremental, taking time for transformation to be observed. Second, coaching for social change – an emerging field in coaching – challenges the traditional paradigms of the role of the coach; this finding was tested during coaching, as the coach could not always remain neutral on personal worldviews. Third, the research findings suggest that leaders need support in dealing with workplace challenges related to inclusion and equal opportunities. The lack of transparency perpetuated an environment perceived as extending favouritism and bias. The value of the research is that it demonstrates that shifts in leadership behaviour using transformative learning, however complicated, are possible. It creates opportunities to explore alternate mechanisms of dealing with workplace inclusion, other than traditional organisational development initiatives.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Business and Executive Coaching to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: Transformative learning theory; Coaching for equality; Leadership development coaching; SDG-8: Decent work and economic growth